Simplify 8(x + 6) - 10.

Question

Asked 8/19/2016 9:51:50 AM

Updated 8/19/2016 10:33:20 AM

1 Answer/Comment

s

Question

Asked 8/19/2016 9:51:50 AM

Updated 8/19/2016 10:33:20 AM

1 Answer/Comment

Rating

3

8(x + 6) - 10

= (8x) + (48 - 10)

= 8x + 38

= (8x) + (48 - 10)

= 8x + 38

Added 8/19/2016 10:33:19 AM

This answer has been confirmed as correct and helpful.

Evaluate BC for A = 5, B = -4, and C = 2. **Weegy:** .4096 (More)

Question

Updated 8/19/2016 10:18:12 AM

1 Answer/Comment

Evaluate BC for A = 5, B = -4, and C = 2.

-4(2) = - 8

-4(2) = - 8

Added 8/19/2016 10:18:11 AM

This answer has been confirmed as correct and helpful.

Simplify 10(2x + 3) - 20. **Weegy:** 10(2x + 3) - 20 = (10)(2x)+(10)(3) - 20 = 20x + 30 - 20 = 20x + 10 (More)

Question

Updated 8/19/2016 10:32:39 AM

0 Answers/Comments

Simplify 20 + (2 + r). **Weegy:** 20 + (2 + r) =(r)+(20+2) =r+22 (More)

Question

Updated 8/19/2016 10:19:46 AM

0 Answers/Comments

Evaluate (-A) 2 for A = 5, B = -4, and C = 2.
-25
-10
10
25 **Weegy:** (-A)^2 for A = 5 = (-5)^2 = (-5)(-5) = 25 (More)

Question

Updated 8/19/2016 10:17:37 AM

0 Answers/Comments

Which expression is not equivalent to 8 · x · 2 · y?
8x + 2y
16yx
16xy **Weegy:** 8x + 2y is not equivalent to
8 · x · 2 · y. (More)

Question

Updated 8/19/2016 10:24:47 AM

0 Answers/Comments

32,226,850

questions answered

There are no comments.